Impact of Parental Involvement on Academic Performance of Pupils among Primary Schools in Kabiira Sub-County, Mitooma District, Uganda - Stephenson, Ruhindi; Stella Teddy, Kanyesigye; Jackson, Nzarirwehi (Innovare Journal of Education, 2024)
This study assessed the effect of parents’ involvement on the academic performance of pupils among primary schools in Kabiira subcounty Mitooma district - Uganda. Particularly, the study examined factors such as: parents’ academic level, occupation, and their socio-economic level. The sample size was 60 pupils selected based on simple random sampling techniques. Data were collected using a questionnaire and analyzed using SPSS. The findings revealed that educated parents give more support for the academic achievement of pupils. That some occupations do not allow parents time to interact with their children. Parents with good income do not only support their children but also support school development programs. The study concluded that parental involvement was vital for the academic success of pupils. It is recommended that guidance sessions be organized for parents on the importance of their involvement in the education of their children.